2019
DOI: 10.1002/cncr.32169
|View full text |Cite
|
Sign up to set email alerts
|

Tumor downstaging as an intermediate endpoint to assess the activity of neoadjuvant systemic therapy in patients with muscle‐invasive bladder cancer

Abstract: BACKGROUND: Achieving a pathologic complete response (pCR) with neoadjuvant chemotherapy (NAC) in patients with muscle-invasive bladder cancer (MIBC) has been associated with improved overall survival (OS). This study was aimed at evaluating the impact of pathologic downstaging (pDS; ie, a pT stage at least 1 stage lower than the pre-NAC cT stage) on the OS of patients with MIBC treated with NAC. METHODS: The Retrospective International Study of Cancers of the Urothelial Tract (RISC) and the National Cancer … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
28
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 37 publications
(33 citation statements)
references
References 25 publications
4
28
0
1
Order By: Relevance
“…Yet, these rates still remain unsatisfactory. It has been demonstrated that the administration of neoadjuvant chemotherapy (NAC) improves OS in patients with MIBC . However, this treatment modality is associated with grade 3–4 toxicity in slightly >35% of the recipients and some elderly patients may not be ideal candidates for NAC administration.…”
Section: Discussionmentioning
confidence: 99%
“…Yet, these rates still remain unsatisfactory. It has been demonstrated that the administration of neoadjuvant chemotherapy (NAC) improves OS in patients with MIBC . However, this treatment modality is associated with grade 3–4 toxicity in slightly >35% of the recipients and some elderly patients may not be ideal candidates for NAC administration.…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, the traditional classification system can only predict the risk of recurrence and progression of NMIBC but not the risk of MIBC. After radical cystectomy, some muscle invasive bladder cancer patients (MIBCs) benefit from neoadjuvant chemotherapy (NAC), while others do not (14)(15)(16), which cannot be predicted by the traditional classification system. The pathological parameters of the tumor cannot fully reflect the "intrinsic characteristics" of bladder cancer.…”
Section: Traditional Classification and Molecular Subtyping Systemsmentioning
confidence: 99%
“…In most studies, downstaging had an important impact on survival, even neoadjuvant chemotherapy was not performed 4,6,20 . In this study, complete TURBT was related to a higher rate of downstaging, which was from T2/T1 to T1/Ta, and downstaging was not signi cantly associated with oncological outcome signi cantly.…”
Section: Commentsmentioning
confidence: 99%
“…Radical cystectomy (RC) is the standard option for muscle invasive bladder cancer (MIBC) and some high-risk non-muscle invasive bladder cancer (NMIBC). For locally-advanced disease, neoadjuvant chemotherapy is recommended, and downstaging is associated with good prognosis [4][5][6][7][8][9] . For ≤ pT2N0M0 disease, complete TURBT was related to a higher rate of downstaging after RC, and it was associated with good outcomes [10][11][12][13] .…”
Section: Introductionmentioning
confidence: 99%